2020
DOI: 10.1136/bmjgh-2020-002780
|View full text |Cite
|
Sign up to set email alerts
|

How to set up government-led national hygiene communication campaigns to combat COVID-19: a strategic blueprint

Abstract: While large-scale changes in population behaviour are required to reduce the transmission of the severe acute respiratory syndrome coronavirus 2 virus, the emergency context is not conducive to the sort of careful communications planning that would normally be required to meet such a task. Rapid strategic communications planning in a pandemic by governments is, however, possible and necessary. Steps include setting up a dedicated communications task force, mobilising partners and resources, developing a creati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 34 publications
(44 reference statements)
0
10
0
Order By: Relevance
“…Behavior changes may be brought about by government or social demands, or they may be due to the anxiety and stress caused by the COVID-19 pandemic [7,8]. It has been pointed out that the use of lockdowns to combat the COVID-19 pandemic can have serious adverse effects on other health indicators, including obesity [9].…”
Section: Discussionmentioning
confidence: 99%
“…Behavior changes may be brought about by government or social demands, or they may be due to the anxiety and stress caused by the COVID-19 pandemic [7,8]. It has been pointed out that the use of lockdowns to combat the COVID-19 pandemic can have serious adverse effects on other health indicators, including obesity [9].…”
Section: Discussionmentioning
confidence: 99%
“…this might be responsible for the improvement in HbA1c levels that were observed in June 2020. In addition, government, social demands, or anxiety and stress caused by the pandemic could have also led to behavioral changes 9,10) . However, one study has reported that the use of lockdowns can have adverse effects on health indicators 11) .…”
Section: Discussionmentioning
confidence: 99%
“…Based on examples of effective health campaigns (64)(65)(66)(67)(68) and on our own experience, we propose that successfully developing and delivering musical messages to prevent EIDs requires at least four steps: (1) Establishing a task force or working group; (2) Identifying the most critical preventative measures for inclusion in the composition of a "catchy" song that is understandable and relates to the target audience; (3) Delivering the song to identified target audiences with sufficient intensity/frequency; and (4) Monitoring and evaluating the effectiveness of the music campaign.…”
Section: Essential Steps For a Health Music Interventionmentioning
confidence: 99%
“…For many infectious diseases, preventive measures to reduce transmission risks are well-known, including hand washing, social distancing, using personal protective equipment, and sanitation ( 6 , 67 ). In such cases, selecting behaviors to be promoted in songs is relatively straightforward.…”
Section: Essential Steps For a Health Music Interventionmentioning
confidence: 99%